3-(2-Hydroxyethyl)-3-methyl-1-(4-methylbenzoyl)thiourea - Nazzatush Shimar Jamaludin,; Siti Nadiah Abdul Halim,; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The title thiourea derivative, C12H16N2O2S, has a twisted conformation with the dihedral angle between the NC(=S)N and O=CC6 planes being 35.45 (5)°. The observed conformation allows for an intramolecular N-H...O hydrogen bond. In the molecular packing, supramolecular aggregation is based on hydroxy-O-H...O(carbonyl) hydrogen bonding and leads to supramolecular helical chains along the a axis; chains are reinforced by N-methylene-C-H...S and N-methyl-C-H...[pi](arene) interactions. Supramolecular layers in the ab plane are formed as a result of tolyl-methyl-C-H...[pi](arene) interactions.